(untitled) (Eurasian Journal of Engineering and Technology, 2023)
An analysis of the state of drinking water supply in the country indicates that the quality of drinking water in many regions of the country is deteriorating. Among the reasons are the ongoing pollution of water sources, the low level of implementation of modern water treatment technologies, the high deterioration of distribution networks, the regional peculiarities of water supply sources associated with a deficiency or excess of nutrients that have a negative impact on public health. The article examines the analysis of the state of provision of the republic with centralized water supply and sanitation